Abstract in scientific articles: Translation Aspects (Eurasian Journal of Philology Science and Education, 2023)
The paper discusses the principles of writing a scientific abstract and adequate translation of abstracts in accordance with established standards of English-language international communication. For the time being, active integration of Kazakhstani science into the world scientific community is observed. Naturally, the integration process puts forward the tasks of mastering the standards of academic writing and constructing the text of a scientific publication, typical for the Western European traditions of writing a scientific text. For Kazakhstani scientists, addressing the above tasks triggers the process of changing the paradigm of creating a scientific text in the global English-speaking space. Therefore, the description of the change in the paradigm of creating a scientific text and the problems of translation of the scientific text, resulting therefrom, is the purpose of our study.The author’s abstract and keywords serve as a tool of representation in a scientific paper that presents the research insights. An English-language abstract in a scientific article in Kazakhstani scientific publications is the primary and often the only information source for foreign scientists about some research project. Due to the lack of study of the process of translation of a scientific text, including, in particular, an abstract as a scientific text from Kazakh/Russian into English, the research interest in the given issues has been caused.The paper deals with the specifics of abstracts to Kazakh- and English-language scientific papers published in academic periodicals in technical, engineering, and construction spheres, as well as analyzes the errors made by their authors in translating their abstracts into English.Key words: scientific text, scientific abstract, structure, translation, terminology, Kazakh language, English language.